Enhancement of the vibro-acoustic performance of anti-tetra-chiral auxetic sandwich panels using topologically optimized local resonators. (June 2021) - Hosseinkhani, A.; Younesian, D.; Ranjbar, M.; Scarpa, F.
Abstract: This paper focuses on identifying parameters for optimized distributions of local internal resonators to enhance the vibro-acoustic performance of anti-tetra-chiral auxetic sandwich panels. The sandwich panel and its auxetic core are simulated using a full-scale finite element approach. An equivalent homogenized model is then employed to reduce the computational time of the optimization problem. The homogenized model is based on theoretical formulations and verified with the full-scale model. Clusters of resonators are added to the structure to act as local resonators. These resonators are parallel with the through-the-thickness direction of the panel and provide an Absorbing Tuned Auxiliary System (ATAS) to mitigate flexural vibrations over a frequency range. The mechanical parameters of the resonators and the geometrical topology are the design variables. The frequency-dependent radiated mean sound level (RMSL) and the maximum peak value of the Radiated Sound Power Level (RSPL) are two different objective functions for the optimization. The effects of the loading pattern, topology configuration and objective functions on the optimization results are investigated. The use of localized resonators in the anti-tetra chiral sandwich structures can enhance remarkably the sound attenuation of the panels, particularly in the case of local loading conditions. We observe 3.7 and 2.6 dB RMSL attenuations for the local and full coverage sound pressure loadings. In a similar fashion, 15.9 and 11.5 dB attenuation at RSPL peak are also observed in the auxetic panels for the two sound pressure loading conditions.